A Veblenian Dichotomy re-examination of labour brokerage and South African labour market functionality - Haaketa, Bernadatte Tina (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2020)
Labour markets ar ound the world have witnessed a great change in labour relations. The introduction of globa lisation, increased competition and technological advancements has caused business organisations to change their employment methods. While trying to survive and remain profitable, employers have adopted a new form of triangular employment relationship. Thi s form of employment relationship known as labour broking and which forms part of the Temporary Employment Services (TES) involves a relationship between the worker, labour agent (broker) and a client c ompany. Although it may seem like a good strategy for business organisations, the change in employment relationships has had negative effects and contributed to labour market dysfunctionalities . This has resulted in critics of labour broking calling or an end in labour broking and supporters of labour broking asking for better regulation of the industry. Labour markets are me When it comes to analysing labour broking and its impact on labour market functionality in South Africa. Scholars and analysts such as Budlender ( 2013 ) and Bhorat, Lil enstein, Oosthuizen , and Thornton ( 2016 ) have used the Neoclassical , New Institutional Economics and Marxist approach es. The current views on labour broking and the current schools of thought fail to look at the underlying behavioural aspect of labour brokers and the client c ompanies. Hence making it easy for labour brokers and their client companies to continue with their unscrupulous activities. However, this t hesis adapted the Veblenian Dichotomy framework which focuses on understanding the role of the evolutionary proce ss and the role of institutions in shaping economic behaviour. The Veblenian dichotomy shows that power plays an important role in how labour markets are run. Similarly, behaviour also influences the manner in which labour brokers and client companies trea t workers. And lastly the Veblenian dichotomy shows that in order for the industry to be run better there has to be change in the behaviour and cultu re of the labour brokers and client companies . This view allows for deeper analysis of the reasons for the flour ishing nature of labour broking and the rationale behind the behaviour of economic players and attempts to provide solutions on how labour brok ing can be correctly administered in South Africa. The Veblenian Dichotomy categorises institutions into t wo sets, namely the ceremonial institutions and instrumental institutions. Where Ceremonial institutions are said to be institutions that foster the interests of business such as profitability and earning of free income, even if there is no corresponding i ncrease in production. While Instrumental institutions, usually working through the influence of technology, address the interests of the common pers on and the labourer as well as business (Waller, 1982; Foster, 1981; Veblen, 1919). These two systems of va lues and institutions are antagonistic and the relative strength of one to the other determines economic outcomes and in whose interests the outcomes would be (Waller, 1982; Foster, 1981; Veblen, 1919). The Veblenian Dichotomy further looks at ceremonial encapsulation which occurs when ceremonial systems prevail over instrumental systems. Ceremonial encapsulation presents the hypothesis that the insti tutional structure will absorb new technology only to the extent that it can do so without disrupting the e xisting value structure (Waller, 1987; Bush, 1979.) The thesis use d various sources , such as working papers, public hearings, court cases, trade union submissions, integrated reports from companies, employee submissions and media publications on the debate about labour broking whether labour broking and applied the Interpretative Phenomenological Analysi s (IPA) research approach, in the process of data collection and analysis . The thesis further applied thematic analysis to derive themes that would be used to analyse the impact of labour broking on labour market functionality in South Africa. The emergent themes and subthemes were Exploitative lab our relations subthemes; job Insecurity, increased financial burden and no skills development. The second theme was; Competitive advantage and the subthemes were; i ncreased profits and organisational efficiency. The third theme was l abour market efficiency and the subthemes were. E mployment creation and labour market flexibility. And, the last theme was a mbiguous l abour regulation s with subthemes; n o freedom of association and a tool for circumventing labour regulations . Lastly, Tool's (1994) criteria of j udgement for institutional adjustments was used to evaluate the emergent themes and to evaluate the impact of l abour broking on the overall welfare of individuals, which includes determining whether employees in the TES sector gain skills and improved stan dards of living. The findings of the research the TES sector is characterised by ceremonial values. Ceremonial values (as mentioned in section 3.3) are those values that are warranted by the ways of life that prescribe status and hierarchies and unpleasant distinctions to apply value and status on other people (Bush, 1987, 1988; Ayres, 1967). Thus changing the way in which labour brokers conduct themselves or handle labour broking activities would prove to be difficult . T he power that is mostly used in TES employment sectors is condign power. Condign power is explained as the form of power that is predominantly used in ceremonially encapsulated markets. And it involves making use of punishment or fear in order to get people to do something. This is because w orkers in the TES sector are forced to submit to conditions that they would not normally have submitted to if t hey did not have a fear of losing their jobs. This supports existing literature which shows that in the TES sector, TES employers use force and p ower in order to get the workers to do something, and this results in a master - servant relationship between the employer and the employee. Furthermore, the protests that erupt in the TES sector agree with Marxist theory which notes that the frustrations in the way workers are treated would result in a revolution of the working class against the employers. However, now, workers have not been able to overcome the employers and take over the industry. In addition to what current literature says, the research found that some managers make use of labour broking as a way of manifesting their exploitative characteristics on the labour market, thus creating information asymmetries in order to advance their own personal needs. Situations such as these reve al characteristics of opportunistic behaviour, which is perpetuated by the imperfect flow of information. This means th at the market is imperfect, and imperfect markets are characteristics of dysfunctional labour markets. The research also found that it i s the South African Constitution that protects labour brokers and client companies from accounting for the unfair treatm ent of workers. Labour brokers and client companies rely on the South African Constitution to defend them when it comes to banning labou r broking. This is because section 22 of the Constitution talks about the right of every individual to trade freely in S outh Africa (Kutumela, 2015). When institutional adjustments do not meet the requirements of the progressive criteria, it means they are regressive. Based on the data that was collected and the responses and remarks of the workers, trade unions, and trade union federations, it can be said that TES employment and labour broking hinders labour market functionality. Hence, it can be concluded that, due to the characteristics mentioned, labour broking does indeed have a regressive element which hinders labour m arket functionality. An area for further research for TES employment would be to look at the impact of the amendments to the Labour Rela tions Act. Specifically focusing on the Constitutional Court ruling, which forces labour brokers to treat employees who have been employed for longer than three months as permanent employees.
Keywords: Veblen, Thorstein, 1857-1929; Contracting out -- South Africa; Temporary employment -- South Africa; Industrial relations -- South Africa; Labor supply -- South Africa; Labor supply -- Effect of technological innovations on -- South Africa; Manpower policy -- South Africa; Labor market -- South Africa